Quantification of the thermal resistance variation in evaporators surface due to ice formation - Carrilho, Diogo G. (2019)
Refrigeration takes a very important role in society. Nowadays, a big portion of the refrigeration processes are taken into account in the food and drinks storage, and also in the cooling of closed spaces. The method of heat removal from the surrounding air through the evaporation of a fluid, being a process of continuous improving, has suffered many enhancements in order to obtain better energetic consumption levels. One of the main restrictions of the usual refrigeration mechanisms is the icing verified in the external surface of the evaporators, as a part of the refrigeration cycle. The present work discusses the mitigation process of ice formation through a proposed heat exchangers configuration. The experimental unit built for this purpose allows the ice layer formation over the heat exchangers surface for several values of air flow rate, temperature and relative humidity. The evaluation of the thermal resistance of the heat exchangers surface together with the condensates collected provides an insight of the consequences of the different air conditions and of the proposed configurations on the ice formation process.